Influence of large‐scale climate modes on daily synoptic weather types over New Zealand. (17th February 2012) - Jiang, Ningbo; Griffiths, Georgina; Lorrey, Andrew
Abstract This article examines the influence of El Niño Southern Oscillation (ENSO), Southern Annular Mode (SAM) and Interdecadal Pacific Oscillation (IPO) on the synoptic weather types over New Zealand. The effects of ENSO (indicated by the Southern Oscillation Index, SOI), SAM and IPO on the occurrence of synoptic types are estimated in a holistic framework using the maximum likelihood method via applications of generalized linear models, both annually and by seasons. The average within‐class variations in the intensity and air‐mass characteristics (as expressed in the Auckland Airport meteorological variables) of synoptic systems were examined for individual types at the annual level. The results show that ENSO, SAM and IPO have significant effects on the probability of occurrence and to lesser degree the intensity and air‐mass characteristics of some synoptic types. The effects vary considerably with seasons, synoptic types and phases of SOI, SAM and IPO and it is the confounding effects of different large‐scale modes that lead to the observed changes in the type frequencies. The findings, with respect to ENSO and SAM in all cases and for IPO at the seasonal level, are in good agreement with the literature. However, the annual changes in type frequencies associated with the 1976/1977 IPO phase shift do not support the observed changes in the strength of anomalous southwesterly windflows over New Zealand, and the influence of the recent negative IPO phase also appears different from what we expect based on the existing research. It appears that the interaction between IPO and ENSO is important for understanding the observed climatic effects of IPO on New Zealand's weather and climate. This aspect deserves further attention in future studies. The findings from this work have important methodological and practical implications for New Zealand climate research. Copyright © 2012 Royal Meteorological Society